Analisis Pelaksanaan Program Penguatan Karakter Implementasi Kurikulum 2013 - Linda Furwanti (Universitas PGRI Adi Buana Surabaya, 2020)
This study aims to describe the implementation and evaluation of Character Strengthening Program (PPK) in Elementary Schools. The research approach used is the case study method. Research subjects were the principal, 3 teachers, and 9 students. Data collection techniques using questionnaires, interviews and observations. The results of this study concluded the strengthening of religious character Program was carried out integrated with several programs such as recitation, habituation of duha prayer, and memorization of the Qur'an. Strengthening nationalism character Program through routine flag ceremony activities every Monday, and scout extracurricular activities. Strengthening independent character Program, namely students making class rules. Strengthening mutual Program character Program, that is, students help each other in doing each activity. Strengthening character integrity Program, that is, students are responsible for doing learning and in activities outside the classroom. The Character Strengthening Program (PPK) which is run at one of the elementary schools in the city of Semarang has been running well according to the school concept and the Ministry of Education and Culture.